Help!!!!!!!!!!!!!!!!!
![Help class=](https://us-static.z-dn.net/files/df7/457f0e85c653d7bd138f12683e6c6d7f.png)
Answer:
x= -2
Step-by-step explanation:
3(2x-4)= -24
expand
6x-12= -24
6x= -24+12
6x= -12
x= -12/6
x= -2
Answer:
x=-2
Step-by-step explanation:
To solve the equation, we must get x isolated on one side of the equation.
[tex]3(2x-4) = -24[/tex]
3 is being multiplied by 2x -4. The inverse of multiplication is division. Divide both sides of the equation by 3.
[tex]\frac{3(2x-4)}{3} = -\frac{24}{3}[/tex]
[tex](2x-4)= -\frac{24}{3}[/tex]
[tex](2x-4)= -8[/tex]
4 is being subtracted from 2x. The inverse of subtraction is addition. Add 4 to both sides of the equation.
[tex]2x-4 +4 = -8+4[/tex]
[tex]2x= -8+4[/tex]
[tex]2x= -4[/tex]
x is being multiplied by 2. The inverse of multiplication is division. Divide both sides by 2.
[tex]\frac{2x}{2} =\frac{-4}{2}[/tex]
[tex]x=\frac{-4}{2}[/tex]
[tex]x= -2[/tex]
Let's check our solution. Plug -2 in for x and solve.
[tex]3(2x-4)= -24[/tex]
[tex]3(2(-2)-4)= -24[/tex]
[tex]3(-4-4) = -24[/tex]
[tex]3(-8)= -24[/tex]
[tex]-24=-24[/tex]
The statement above is true, so we know our solution is correct.
The answer to the equation is x= -2.